CRISPR-Cas9 screening develops an epigenetic and transcriptional gene signature for risk stratification and target prediction in neuroblastoma - Zhang, Liaoran; Mo, Jialin; Shi, Hao; Xiong, Jing; Aierken, Yeerfan; Chen, Feng; Tang, Yujie; Zhao, Kewen; Lv, Zhibao; Tan, Kezhe (Frontiers in Cell and Developmental Biology, 2024)
Objectives: Neuroblastoma (NB), a pediatric malignancy of the peripheral nervous system, is characterized by epigenetic and transcriptional (EP-TF) anomalies. This study aimed to develop an EP-TF clinical prognostic model for NB using CRISPR-Cas9 knockout screening. Results: An integrative analysis was conducted using CRISPR-Cas9 screening in vitro and in vivo with public NB datasets to identify 35 EP-TF genes that exhibited the highest expression in NB and were highly dependent on cancer viability. After univariate analysis, 27 of these 35 genes were included in the least absolute shrinkage and selection operator screen. We established and biologically validated a prognostic EP-TF model encompassing RUVBL1, LARP7, GTF3C4, THAP10, SUPT16H, TIGD1, SUV39H2, TAF1A, SMAD9 and FEM1B across diverse NB cohorts. MYCN serves a potential upstream regulator of EP-TF genes. The high-risk subtype exhibited traits associated with the malignant cell cycle, MYCN-linked signaling and chromatin remodeling, all of which are correlated with poor prognosis and immunosuppression. MEK inhibitors have emerged as promising therapeutic agents for targeting most EP-TF risk genes in NB. Conclusions: Our novel prognostic model shows significant potential for predicting and evaluating the overall survival of NB patients, offering insights into therapeutic targets. Keywords: neuroblastoma, epigenetic and transcriptional genes, prognostic model, MYCN, drug targets.